2021
DOI: 10.1080/20961790.2021.1940737
|View full text |Cite
|
Sign up to set email alerts
|

Eye tracking and child sexual offenders: a systematic review

Abstract: Eye tracking is used in sexology to identify attractiveness and sexual desire indirectly. This systematic review summarizes results of works that have used eye tracking to analyse paedophilic interest in order to investigate its potential as a useful forensic tool. Six studies met the inclusion criteria. Five of them concerned a large study project and used approximatively the same sample of paedophiles (inpatients), forensic patients (without a sexual interest in children) and healthy controls to make compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…A more comprehensive review of the results of research using eye-tracking to analyze pedophilic interest can be found in Godet and Niveau [ 88 ], who identified only six studies with this objective, including those mentioned above. The authors conclude that although the results suggest that eye-tracking is useful for discriminating between men with pedophilic sexual interests from non-pedophiles, there is limited research on this topic, with small and diverse samples, and more clarity is needed on its relevance in the forensic context.…”
Section: Eye-tracking and Atypical Sexual Preferences: Empirical Evid...mentioning
confidence: 99%
“…A more comprehensive review of the results of research using eye-tracking to analyze pedophilic interest can be found in Godet and Niveau [ 88 ], who identified only six studies with this objective, including those mentioned above. The authors conclude that although the results suggest that eye-tracking is useful for discriminating between men with pedophilic sexual interests from non-pedophiles, there is limited research on this topic, with small and diverse samples, and more clarity is needed on its relevance in the forensic context.…”
Section: Eye-tracking and Atypical Sexual Preferences: Empirical Evid...mentioning
confidence: 99%
“…Eye-tracking has been used to observe if the accused's gaze patterns match those of patients with schizophrenia, to assess the validity of an insanity defense (Ales, Giromini et al 2021). In another example, eye-tracking was used to observe preferential attention to sexualized stimuli to identify pedophile intentions in sexual offenders (Godet and Niveau 2021). Finally, eye-tracking has been employed in an exploratory study to make the decision-making process of 39 active shop-lifters visible (Jacques, Lasky et al 2015).…”
Section: A Identifying Differential Patterns Of Eye-gaze As Indicator...mentioning
confidence: 99%
“…Outside cyber crime, eye-tracking evidence might at most be used to probe the defendant on proclivity towards certain mental processes. The eye-tracking studies with convicted sexual offenders reported in the introduction go into that direction (Godet and Niveau 2021). But in criminal law there is the presumption of innocence.…”
Section: Mental Process As a Precondition For Legal Interventionmentioning
confidence: 99%